(untitled) (Movimenta (ISSN 1984-4298), 2022)
This scoping review aimed to gather scientific information comparing the efficiency of modern extractive methods applied to medicinal plants with the traditional Soxhlet method. The purpose is to help decision-making on the choice of more efficient, simple, cheap, safe and sustainable extraction methods. To this end, the following were established: the guiding question of the research, the descriptors, the databases, and the eligibility criteria for the selection and analysis of the articles. Of 407 results identified by the research, 35 studies met the inclusion criteria. Studies have shown that even if the extraction in Soxhlet apparatus presents a high extraction efficiency of bioactive compounds in medicinal plants, the modern extractive processes, such as ultrasound- and microwave-assisted extraction are cheap, simple, and sustainable alternatives with similar or higher extractive efficiency.